Financial Leverage and Firm Performance in Islamic Banks: A Signal Theory Approach - Suchi Avita Rici; Rahmat Wahyudi (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Financial leverage is one of the main factors affecting overall company productivity, so its existence cannot be ignored. Currently, there is a wealth of literature discussing leverage in various companies in different regions. Meanwhile, Islamic banking is a growing sector that is attracting the interest of researchers. However, there are still few studies that specifically discuss financial leverage in the context of Islamic banks. Therefore, this study aims to evaluate the effect of financial leverage on the performance of Islamic banks. This study also aims to examine the application of signaling theory in assessing the impact of financial leverage on company performance. The population used in this study is Islamic banks listed on the Indonesia Stock Exchange (IDX) from 2015 to 2024. The sampling technique used in this study is purposive sampling, resulting in 11 Islamic banks with 110 observations. The analysis method used is panel data regression analysis. Researcher deployed latest version of E-views for data analysis in current study. The results of this study provide strong evidence to support Signaling Theory. This theory states that a bank's performance will be much better if it has higher capital. The results of the study show that in Islamic banks, financial leverage is at a level that is entirely dependent on the flexibility ratio to adjust their debt and earnings power.